Metabolic preference studies in cells of the tumor microenvironment - Ocaña Farfán, María del Carmen; Martínez-Póveda, Beatriz Amparo; Rodríguez-Quesada, Ana María; Medina-Torres, Miguel Ángel (My University, 2016)
In the last years, the rediscovery of the Warburg effect and high tumoral glutaminolysis has lead to a renewed interest in cancer metabolism. Moreover, recent studies have put some importance in endothelial cells metabolism. Inquiring into the metabolism of accompanying cells of the tumor microenvironment, such as endothelial and immune cells, could shed some light in the search for alternative cancer therapeutic approaches. In this work the use of glucose, glutamine and palmitate as metabolic fuels by endothelial and tumoral cells is studied. In addition, we also test if two antiangiogenic compounds previously described by our group are able to modify key steps of endothelial and/or tumor cells metabolism
Keywords: Cáncer; Células - Metabolismo; Angiogénesis; Tumor microenvironment; Metabolic reprogramming